The Effect of Problem Based Learning Model on Students Learning Outcomes in the "Belajar dan Pembelajaran" Course - Arif, Nely; Volya, Duti; Fajaryani, Nunung; Albert, Albert (Modality Journal: International Journal of Linguistics and Literature, 2022)
Problem Based Learning Model is a learning model that is intensively promoted at the University of Jambi at this time. This study aims to determine whether there is a significant effect on the learning outcomes of English study program students taught with the Problem Based Learning Model in the course of "Belajar dan Pembelajaran (Learning and Instruction). The research design used is Quasi-Experimental Research. This design involves two groups: one as the control group and one as the experimental group. The data obtained from this research is processed by calculating the gain or difference between the pretest and post-test scores. For time efficiency, data were analyzed using the SPSS (Statistical Product and Service Solution) program for Windows version 24. Because of the Asymp value. Sig. (2-tailed) 0.381, which means greater than 0.025, it can be decided that H0 is accepted. So it can be concluded that the PBL learning model used in the experimental class is not effective enough to improve student learning outcomes in â€œBelajar dan Pembelajaranâ€ courses.Model Problem Based LearningÂ  merupakan model pembelajaran yang sedang gencar-gencarnya digalakkan di Universitas jambi saat ini. Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh signifikan antara hasil belajar mahasiswa prodi bahasa Inggris yang diajarkan dengan Model Pembelajaran Problem Based Learning pada mata kuliah â€œBelajar dan Pembelajaranâ€. Desain penelitian yang digunakan adalah Quasi-Eksperiment Research atau Eksperimen semu. Desain ini melibatkan dua grup. Satu sebagai grup kontrol dan satu sebagai grup eksperimen. Pengolahan Data untuk data yang diperoleh dari pada penelitian ini adalah dengan cara menghitung gain atau selisih antara skor pretest dan postest. Untuk efisiensi waktu, pengolahan data dianalisa dengan menggunakan program SPSS (Statistical Product ang Service Solution) for windows versi 24. Karena nilai Asymp. Sig. (2-tailed) 0,381 bearti lebih besar dari 0,025, maka bisa diputuskan H0 diterima. Jadi dapat disimpulkan bahwa model Pembelajaran PBL yang digunakan dikelas eksperimen tidak cukup efektif untuk meningkatkan hasil belajar mahasiswa pada mata kuliah Belajar dan Pembelajaran.